(untitled) - Jensen, Arthur D. (Belmont, Calif., 1991)
his text approaches the study of group communication as skill development integrated with current research. It is written for the beginning student who needs to develop the skills for effective group interactions, yet it seeks to show the student that research and theory are relevant to developing effective behaviors in groups. The goal of the text is that students be able to evaluate group behavior and prescribe techniques for improving group interactions, thus improving the quality of decisions made in groups. The text includes a Rhands onS manual for guiding group meetings, the Group Process Facilitator, as well as a synthesis of the most current research in the field in language that students will understand
Keywords: Communication in small groups,Group relations training,Kỹ năng giao tiếp nhóm